n-dimensional Laplace transforms of occupation times for spectrally negative Lévy processes - Xuebing Kuang; Xiaowen Zhou (Risks, 2017)
Using a Poisson approach, we find Laplace transforms of joint occupation times over n disjoint intervals for spectrally negative Lévy processes. They generalize previous results for dimension two.
Keywords: 330; spectrally negative Lévy process; occupation time; scale function